Firm Value and Entity Choice in Closely Held Business Organizations: Do Taxes Play a Role? - Cooper, John (Journal of Applied Business and Economics, 2021)
This paper examines the role of tax on firm value of closely held businesses. Using sales transactions of closely held business organizations as a proxy for firm value, the double tax system applicable to C corporations versus the single level of tax on passthrough businesses is expected to result in lower firm value for passthrough entities than comparable C corporations. This theoretical assumption is based on increased pricing flexibility available for firms facing a single level of tax over that of entities subject to double taxation. A dataset of nearly 30,000 closely held business sales was evaluated to find that passthrough entities are associated with lower firm value than comparable C corporations. This finding is important since prior research has produced conflicting results. This study contributes to the literature by examining a more comprehensive dataset, including all forms of passthrough entities, and improving the methodology used in earlier studies.